PENGEMBANGAN RENCANA STRATEGIS SISTEM INFORMASI DAN TEKNOLOGI INFORMASI PADA DINAS KESEHATAN MENGGUNAKAN MODEL ZACHMAN FRAMEWORK - Juraidin Juraidin; Chandra Wisnu Nugroho; Leonard Maramis (Universitas Widya Nusantara, 2024)
The Information Systems Strategic Planning (ISSP) aims to align the information system's activities with the organization’s strategic goals. Effective control tools are essential to manage risks associated with organizational, policy, and position changes, ensuring the performance and success of SI/IT implementation. Developing the SI/IT Strategic Plan for the Health Office requires active stakeholder support, involvement, and commitment to achieve the organization's vision and mission. This research aims to create an SI/IT Strategic Plan using the Zachman Framework as a guide. A qualitative case study approach was employed, with problem identification and needs analysis conducted through SWOT analysis, Value Chain, and McFarlan Grid. While the Information System at the Bima Regency Health Office is relatively adequate, it lacks integration and requires development in IT human resources, infrastructure, networks, governance, Standard Operating Procedures (SOPs), stakeholder commitment, financial support, and regulations. Addressing these gaps involves preparing a comprehensive portfolio of planning, policies, infrastructure, and applications tailored to organizational needs. The study concludes that the Bima Regency Health Office requires new or improved systems to support its services. The SI/IT Strategic Plan (2016-2020) includes developing data centers, information systems, infrastructure, network security, human resources, and management processes.